2021
DOI: 10.1371/journal.pone.0251017
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of investigating the association between bacterial pathogens and oral leukoplakia in low and middle income countries: A population-based pilot study in India

Abstract: Background Certain oral bacterial pathogens may play a role in oral carcinogenesis. We assessed the feasibility of conducting a population-based study in India to examine the distributions and levels of Porphyromonas gingivalis, Fusobacterium nucleatum and Prevotella intermedia in relation to oral leukoplakia (a potentially malignant disorder) and other participant characteristics. Methods This exploratory case-control study was nested within a large urban Indian cohort and the data included 22 men and women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The selection of studies included is presented in Figure 1. Table 2 presents key information on seven studies [13][14][15][16][17][18][19] on the association between oral microbiota and oral leukoplakia included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of studies included is presented in Figure 1. Table 2 presents key information on seven studies [13][14][15][16][17][18][19] on the association between oral microbiota and oral leukoplakia included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Each study is identified by a study ID, along with details such as the year of publication, country where the study was conducted, sample size (n), gender ratio, and mean age in years. [18], and Shridhar et al [19] examined the relationship between oral microbiota and leukoplakia using different methodologies and assessments. The studies varied in terms of the specific microbial species or taxa assessed within the leukoplakia patient population.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, other saliva-based studies were able to identify significant differences in the microbiome composition between OLK and healthy controls [12,[15][16][17][18]. Moreover, although through a highly biased study (i.e., time lag between OLK and sampling; lack of histologic assessment of OLK), Shridhar et al showed a better proportion of quantifiable pathogens from salivary rinse rather than gingival swabs for three selected species [18].…”
Section: The First Dilemma: What To Samplementioning
confidence: 99%
“…Based on previous reports, Shridhar et al did not investigate the whole microbiome in their population-based study. Instead, they focused on three renowned bacterial pathogens: Porphyromonas gingivalis, Fusobacterium nucleatum and Prevotella intermedia [18].…”
Section: The Foreground: Bacteriamentioning
confidence: 99%